Nuclear fragments of the neural cell adhesion molecule NCAM with or without polysialic acid differentially regulate gene expression - Westphal, Nina (Sci Rep, 2017)
The neural cell adhesion molecule (NCAM) is the major carrier of polysialic acid (PSA) which modulates NCAM functions of neural cells at the cell surface. In previous studies, we have shown that stimulation of cultured neurons with surrogate NCAM ligands leads to the generation and nuclear import of PSA-lacking and -carrying NCAM fragments. Here, we show that the nuclear import of the PSA-carrying NCAM fragment is mediated by positive cofactor 4 and cofilin, which we identified as novel PSA-binding proteins. In the nucleus, the PSA-carrying NCAM fragment interacts via PSA with PC4 and cofilin, which are involved in RNA polymerase II-dependent transcription. Microarray analysis revealed that the nuclear PSA-carrying and -lacking NCAM fragments affect expression of different genes. By qPCR and immunoblot analysis we verified that the nuclear PSA-carrying NCAM fragment increases mRNA and protein expression of nuclear receptor subfamily 2 group F member 6, whereas the PSA-lacking NCAM fragment increases mRNA and protein expression of low density lipoprotein receptor-related protein 2 and α-synuclein. Differential gene expression evoked by nuclear NCAM fragments without and with PSA indicates that PSA-carrying and -lacking NCAM play different functional roles in the nervous system.